Sistema de eletrificação de gotas e eficiência da pulverização eletrostática no controle do psilídeo Triozoida limbata (Enderlein) (Hemiptera : Triozidade) em goiabeira (Psidium guajava L.) - Tavares, Rafael Marcão (2015)
Spray technologies have been studied to increase efficacy of pesticide treatments, such as electrostatic spraying. In this technology, spray droplets are electrified to be attracted by the spray targets. However, factors that affect the efficacy of this technology, such as relation charge/mass (Q/M), need to be better analyzed. This study evaluated factors that affect the performance of a droplet electrification system, and compared its efficacy with a conventional spraying technology on the chemical control of guava psyllid. The study was divided in two parts, in which a backpack sprayer containing an electrostatic kit with indirect induction electrification was analyzed. The first part, with three experiments in completely randomized design, studied, in Faraday cage with a multimeter, the effect of application rates, of the distance between the nozzle and the target, and of the mixture composition in the relation Q/M generated by the electrostatic system. Application rates between 0.2 and 1.6 L min-1 were evaluated in the first experiment. Four distances (0, 0.5, 1 and 2 m) between the nozzle and the cage were analyzed in the second one. Five tank mixtures (water, mineral oil, vegetable oil, spreader adhesive and insecticide) and five rates were evaluated in the third experiment. Grater flow rates imply in a reduction of the relation Q/M, which was also observed with increasing distances between nozzle and target. The composition of tank mixtures also can affect the relation Q/M. The second half of the research was done with two simultaneous experiments, both in two seasons, to evaluate the control of the psyllid and the performance of spraying technologies. The first study, in randomized blocks, with five treatments (control with no spray; 600 L ha-1 in a conventional air spraying, and 300, 200 and 100 L ha-1 with electrostatic spraying), evaluated the percentage of infested leaves and the pest population. The second study, in split plots and randomized blocks, evaluated the same technologies of the previous study and plant quadrants (Q1, Q2, Q3 and Q4) in the sub plots for the deposition of the mixture on the leaves, mixture losses to soil in Petri plates, and droplet spectra in hydro-sensitive paper. Evaluation of deposition and losses was done by adding Brilliant Blue dye to the spraying mixture, and subsequent detection by absorption in spectrophotometry. Data obtained was divided by the respective leaf or plate areas. Deposition was twice as greater and losses four times smaller in electrostatic spraying than in the conventional technology. Only the electrostatic spraying resulted in smaller infestation percentage in relation to the control. All technologies reduced pest population. It can be concluded that electrostatic spraying is more effective, allowing a reduction of spraying rates with no loss of control of the guava psyllid.